Statins for the prevention and treatment of acute lung injury and acute respiratory distress syndrome: A systematic review and meta‐analysis. Issue 6 (24th May 2016) - Xiong, Bo; Wang, Chunbin; Tan, Jie; Cao, Yin; Zou, Yanke; Yao, Yuanqing; Qian, Jun; Rong, Shunkang; Huang, Yuwen; Huang, Jing
Abstract: The purpose of this meta‐analysis was to assess whether statins could reduce the morbidity of acute lung injury and acute respiratory distress syndrome (ALI/ARDS) in high‐risk patients and improve the clinical outcomes of patients with ALI/ARDS. Studies were obtained from PubMed, Medline, Embase and Cochrane Central Register of Controlled Trials. Randomized controlled trials (RCTs) and cohort studies, which reported morbidity, mortality, ventilator‐free days, length of stay in intensive care unit and hospital or oxygenation index, were included in our meta‐analysis. Risk ratio (RR) and weighted mean difference (WMD) were calculated using fixed or random effect model. A total of 13 studies covering 12 145 patients were included. Both the only RCT ( P = 0.10) and cohort studies (RR, 1.02; 95% CI, 0.67 to 1.55; P = 0.94) showed that statin therapy did not lower the morbidity of ALI/ARDS in high‐risk patients. The mortality of ALI/ARDS patients was less likely to be improved by statins (RCT, RR, 1.00; 95% CI, 0.84 to 1.20; P = 0.97; cohort studies, RR, 1.04; 95% CI, 0.85 to 1.27; P = 0.72). Moreover, no significant difference was observed in ventilator‐free days, length of stay in intensive care unit as well as hospital and oxygenation index. This meta‐analysis suggests that statins neither provide benefit for lowering the morbidity of ALI/ARDS in high‐risk patients nor improve the clinical outcomes of ALI/ARDS patients. Hence, it may not be appropriate to advocate statin use for the prevention and treatment of ALI/ARDS.